2021
DOI: 10.3389/fpsyt.2021.700493
|View full text |Cite
|
Sign up to set email alerts
|

Family Care, Economic Stress, and Depressive Symptoms Among Chinese Adults During the COVID-19 Outbreak: Difference by Urban and Rural Areas

Abstract: Background: Although several studies have shown an association of family care with a high level of depressive symptoms, the relationship between them remains indistinguishable.Objective: This study aims to examine the associations between family care, economic stress, and depressive symptoms among Chinese adults in urban and rural areas during the COVID-19 outbreak.Methods: Based on cross-sectional data collected through online surveys from February 1st to 10th 2020 in China the present study recruited 2,858 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…All of these findings were consistent with previous studies in China and other countries (7,20,48). Comparing with the rural region, people who live in the urban region have heavier work-load and life stress (49,50), and they may be at higher risk of mental disorders. Substance use disorders, one way to deal with stress, maybe also in higher-level for rural residents.…”
Section: Resultssupporting
confidence: 91%
“…All of these findings were consistent with previous studies in China and other countries (7,20,48). Comparing with the rural region, people who live in the urban region have heavier work-load and life stress (49,50), and they may be at higher risk of mental disorders. Substance use disorders, one way to deal with stress, maybe also in higher-level for rural residents.…”
Section: Resultssupporting
confidence: 91%
“…Two studies categorised carers as new carers or continued/existing carers [ 41 , 46 ], one study had a very broad definition of caregiving [ 46 ], whilst the other restricted their caring exposure to out-of-home caregiving [ 41 ]. One study divided carers into short-term and long-term (>12 months) caregivers [ 44 ], whilst another examined childcare and eldercare separately as well as together (sandwich care) [ 54 ]. Two studies inferred caregiving based on family/household composition.…”
Section: Resultsmentioning
confidence: 99%
“…Every included study utilised a validated measure of MH (in line with the review criteria), all of which were self-reported via survey-based instruments. Seven studies examined depression and anxiety as two separate MH outcomes [ 43 , 47 49 , 52 , 53 , 60 ], whilst twelve studies examined only depression/physiological distress [ 41 , 42 , 44 46 , 50 , 54 59 ], and one study examined only anxiety [ 51 ]. A descriptive summary and main findings of included studies (including effect estimates and confidence parameters where reported) can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, retrenchment following the economic fallout of the pandemic may be particularly stressful for middle-aged adults, who may struggle with reemployment (e.g., Chiu & Ho, 2006; Oh, 2020) with retirement still some time away. Further, middle-aged adults may be tasked with demanding caregiving responsibilities of their elderly parents (e.g., Liu et al, 2021; Putro & Riyanto, 2020), which have been made more challenging by the pandemic (Liu et al, 2021; Phillips et al, 2020). For older adults, they are likely to live alone due to factors such as widowhood or their adult children moving away (Tang et al, 2019).…”
Section: Covid-19 Depression and Activity Engagementmentioning
confidence: 99%